Sustainable Agricultural Development Economics and Policy (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The sustainable development of agriculture is not only dependent on economics and policy but also relies on decisions to increase sustainability through either (1) specialization (e.g., sustainable intensification) or (2) diversification (e.g., ecological intensification). Understanding the historical context of the region being evaluated is critical to selecting ideal development strategies. Depending on the emphasis on either specialization or diversification, sustainable development can follow different pathways. Specialization during agricultural development is typically concentrated in specific geographic areas with comparative advantages in terms of agricultural production. However, tradeoffs to agricultural specialization include greater reliance on purchased external inputs, greater dependence on government support, and international and interregional interdependence. Addressing the economic and environmental challenges of specialized agricultural production requires a focus on detailed models and field experiments to help balance productivity with reduced environmental impacts. Diversification can incorporate both enterprise diversification as well as ecological intensification strategies, such as integrating livestock and agroforestry with crops. Despite the promises of maintaining the diversity of small shareholders in the developing world, challenges remain. Regional case studies can be used to inspire and implement diversified agricultural systems for the creation of more sustainable future food systems around the world.